Explore the Usefulness of Concurrent Chemotherapy in Stage II Nasopharyngeal Carcinoma: A Retrospective Study - Li, Pei-Jing; Lai, Yu-Lin; He, Fang; Chen, Yuan-Yuan; Gu, Zhuo-Sheng; Luo, Wei; Zhang, Qun (Frontiers in Pharmacology, 2021)
Objective: This study aims to compare the efficacy of concurrent chemoradiotherapy (CCRT) versus radiotherapy (RT) alone in patients with stage II nasopharyngeal carcinoma (NPC). Methods: This study retrospectively collected 601 patients with stage II NPC treated in two hospitals between June 2003 to June 2016. All patients were divided into the CCRT group (n=255) and the RT group (n=346). Overall survival (OS), loco-regional relapse-free survival (LRFFS), progression-free survival (PFS), and distant metastasis-free survival (DMFS) were assessed using the Kaplan-Meier method. The log-rank test was used to compare the differences between the groups. The Cox-regression hazards model was performed to determine potential prognostic factors. Results: The median follow-up was 99 months. No significant difference was found in loco-regional recurrence, distant metastasis, and disease progression between the two groups (all P>0.05). The 5-year OS, PFS, LRFFS, and DMFS for the CCRT group were not superior to that of the RT group (all P>0.05). Two-dimensional radiotherapy (2DRT) subgroup analysis showed concurrent chemotherapy could remarkably improve DMFS, PFS, and OS (all P<0.05) but not LRFFS (P=0.258). While intensity-modulated radiotherapy (IMRT) subgroup analysis showed the prognosis of the two groups had no significant differences (all P>0.05). In multivariable analyses, age was an independent risk factor for OS, PFS, LRFFS, and DMFS and inversely related to them. IMRT was an independent favorable factor for improving LRFFS, PFS, and OS. Concurrent chemotherapy was an independent protective factor of DMFS and had a trend to increase PFS and OS. Conclusion: In the context of 2DRT, it is definite that concurrent chemotherapy provides survival benefits for patients with stage II NPC. While under the background of IMRT, concurrent chemotherapy significantly improves distant metastasis-free survival and tends to reduce the risk of disease progression and death. Multicenter prospective randomized controlled studies are required to confirm these results.